2019
DOI: 10.1002/adem.201900479
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Twinning and Detwinning in Face‐Centered Cubic Metallic Materials

Abstract: Deformation twinning and detwinning are widely observed in face‐centered cubic (FCC) metallic materials processed by severe plastic deformation. Several twinning and detwinning mechanisms are reported in coarse‐grained and nanocrystalline materials. In this article, the mechanisms for deformation‐induced twinning and detwinning in FCC metallic materials, factors affecting twinning propensity, and grain‐size effect on the competition between twinning and detwinning are reviewed. The effects of twinning and detw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 91 publications
(268 reference statements)
0
19
0
Order By: Relevance
“…The blue circle in Figure 4 b shows a ledge occurring in the twin laminar crystal in the strained nt-Cu film. It has been proposed that the ledge is formed by the accumulation of the dislocations on the twin-boundary [ 44 , 45 ]. Typically, those dislocations belong to type-I and type-II slip systems, which are discussed in the previous section.…”
Section: Resultsmentioning
confidence: 99%
“…The blue circle in Figure 4 b shows a ledge occurring in the twin laminar crystal in the strained nt-Cu film. It has been proposed that the ledge is formed by the accumulation of the dislocations on the twin-boundary [ 44 , 45 ]. Typically, those dislocations belong to type-I and type-II slip systems, which are discussed in the previous section.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that mechanical twinning and detwinning operate in nanocrystalline FCC metals [3][4][5]. The dislocation-twin interactions potentially responsible for each of those two phenomena have been analyzed in detail [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the strengthening of twin-structured metals results from dislocations intersecting with coherent twin boundaries (CTBs), which was confirmed by both molecular dynamics (MD) simulations and experimental investigations [1,5,6,[9][10][11][12]. In contrast, for the softening mechanism, in situ atomic-scale observations of the detwinning process have rarely been studied, especially for twinstructured nanocrystalline (NC) metals with grain sizes of 15 nm [3,9,10,[13][14][15][16]. In addition to dislocation-CTB intersection, several MD simulations and experiments have indicated that detwinning can also significantly affect the mechanical properties of twin-structured metals [7,10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dislocation-CTB intersection, several MD simulations and experiments have indicated that detwinning can also significantly affect the mechanical properties of twin-structured metals [7,10,11,17]. The atomicscale mechanism of detwinning is crucial, which may provide clues for designing twin-structured metals with high strength and excellent ductility [1,10,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%